The Effect of Topical Vitamin D and Olive Oil on Xerosis and Pruritus in HD Patients - Achmad Fauzi; Rima Yulia; Tangguh Panji Saputra; Ajeng Handaru Putri; Wahyu Agung Dwi Saputra (Jurnal Penelitian Pendidikan IPA, 2024)
The kidneys are essential organs maintaining the body's stability. Chronic Kidney Disease (CKD) causes 850,000 deaths yearly, ranking it 12th among global causes of death. This number is projected to rise, reaching 14 per 100,000 people by 2030. This study used a quantitative quasi-experimental design with a one-group pretest-posttest approach from June 13 to July 13, 2024. The study involved 42 respondents, and paired t-test analysis revealed significant effects of applying topical Vitamin D and olive oil on xerosis and pruritus in hemodialysis patients in West Java hospitals (T-Count: 23.854 > T-table: 0.462, p-value: 0.045). Most respondents were aged over 50 (66.9%) and predominantly male (61.9%). Hemodialysis duration varied, with 32.3% treated for less than 12 months and 47.7% for over 12 months. Comorbidities were present in 88% of respondents. After treatment, no patients reported severe itching from xerosis or pruritus. In conclusion, the study shows that topical Vitamin D and olive oil significantly reduce xerosis and pruritus in hemodialysis patients in West Java (p-value: 0.045).